Biodegradability, cellular compatibility and cell infiltration of poly(3-hydroxybutyrate-co-4-hydroxybutyrate) in comparison with poly(ε-caprolactone) and poly(lactide-co-glycolide). (March 2015) - An, Jun; Wang, Kai; Chen, Siyuan; Kong, Meimei; Teng, Yuxin; Wang, Lianyong; Song, Cunjiang; Kong, Deling; Wang, Shufang
Poly(3-hydroxybutyrate-co-4-hydroxybutyrate), poly(ε-caprolactone), and poly(1actide-co-glycolide) films were prepared by solution casting and electrospinning. The degradability of cast films was evaluated in vitro and in vivo by recording the weight remaining, observing the morphology, and measuring change in molecular weight and M w / M n polydispersity. In addition, cell proliferation on electrospun films was tested by MTT assay, and cell infiltration into electrospun films was assessed through subcutaneous implantation in rats. By analyzing data obtained from these tests, we discovered that the degradation rates of poly(3-hydroxybutyrate-co-4-hydroxybutyrate) copolymers were between those of poly(ε-caprolactone) and poly(1actide-co-glycolide) and could be controlled by adjusting 4-hydroxybutyrate content. Moreover, tissue responses to materials made from poly(3-hydroxybutyrate-co-4-hydroxybutyrate) were milder compared with those elicited by poly(ε-caprolactone) and poly(1actide-co-glycolide), and poly(3-hydroxybutyrate-co-4-hydroxybutyrate) films exhibited a good and moderate cell infiltration. Therefore, our data demonstrate that poly(3-hydroxybutyrate-co-4-hydroxybutyrate) copolymers are promising candidates for the construction of scaffolds designed for various types of tissue regeneration with special biodegradability requirements.